PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DAN LOYALITAS KONSUMEN PADA LAYANAN INTERNET KARTU PRABAYAR SIMPATI PADA MAHASISWA DI JAKARTA - Aji Setyo; Iha Haryani Hatta; M. Nuruddin Subhan (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2021)
ABSTRACT The purpose of this study was to determine the effect of price and product quality on purchasing decisions and consumer loyalty in simpati prepaid internet card services for students in Jakarta. The research design used in this research is descriptive research using a quantitative approach. The analytical method used in this research is path analysis. The type of data used in this study is primary data using a questionnaire. The sample used in this study were 200 respondents. The results showed that price has a negative effect on purchasing decisions, product quality has a positive effect on purchasing decisions, purchasing decisions have a positive effect on consumer loyalty, prices have a negative effect on consumer loyalty, product quality has a positive effect on consumer loyalty. not significant to consumer loyalty, product quality through purchasing decisions has a significant effect on consumer loyalty. Keywords: Price, Product Quality, Purchase decision, Consumer Loyalty